The Social Responsibility of Banks During Financial Crisis Periods: Towards The European Union's Directive on Non-Financial Reporting - Novokmet, Ana Kundid; Bilić, Bruna (Oeconomica Jadertina, 2017)
The current financial crisis reaffirmed the relevance of social responsibility and ethics in financial products. Frauds, scandals, collective law suits by organizations for consumer protection, negative reputations as well as increasing anti-corporate activism have not circumvented the banking industry. In a situation of constant emphasis of social costs and operating damages, the banks are expected to embrace social responsibility more significantly, as well as to endure the sizeable burden of the economic crisis. According to the legitimacy theory, the voluntary adoption of the corporate social responsibility concept within the banking business may serve as a method of building up the reputational capital of the banks and regaining the trust of society in banking products, all segments where it is important that socially responsible actions are adequately reported and disclosed. Thanks to the 5/EU on non-financial reporting of large-sized and listed companies as well as public-interest entities, social responsibility reporting will soon become mandatory for the banking sector. By giving an insight into the scale of social responsibility reporting of selected Croatian banks, this paper will address responsibility reporting has increased during the financial crisis, as the legitimacy theory suggests. It will also give an answer how prepared are banks for the new regulatory requirements in the nonfinancial reporting area.
Keywords: commercial banks; corporate social responsibility; financial crisis; legitimacy theory; internet disclosure